The Childfree Phenomenon in Indonesia: UIN Jakarta Students' Perspectives in Responding to the Contradiction Between Traditional Values and Modernity - Ima Qimmatul Maflahah (Universitas Muhammadiyah Enrekang, 2024)
This study aims to explore the views of Generation Z students on the childfree phenomenon in Indonesia. The method used is a qualitative approach with online in-depth interviews with students of the State Islamic University (UIN) Jakarta. This research uses thematic analysis techniques to understand the interviewees' perspectives. The results showed that childfree is a growing trend with the potential to increase interest in the future. UIN Jakarta students understand childfree as a couple's decision not to have children in marriage, based on various reasons, such as economic considerations, mental health, and individual freedom. However, students' opinions are divided: some support it on the grounds of individual freedom rights, while others reject it because it is considered contrary to the cultural and social values of Indonesian society. Despite the pros and cons, the majority of students agree that childfree is a form of individual freedom in determining their life path